A review of bioinspired computer‐aided design tools for hardware design. (2nd January 2013) - Lanchares, Juan; Garnica, Oscar; Fernández‐de‐Vega, Francisco; Ignacio Hidalgo, J.; Hidalgo, Jose Ignacio; Fernández‐de‐Vega, Francisco; Amor, Margarita; Doallo, Ramón; Fraguela, Basilio B.; Herrero, José R.; Quintana‐Ortí, Enrique S.; Strzodka, Robert
SUMMARY During the tools have been also influenced by this evolutionary fashion. In this paper, we give a broader view of the application of techniques inspired by nature to hardware design and parallel architectures problem solving. Our aim is to furnish an overview of the various bioinspired techniques based tools that have been used so far to solve the problems of automatic hardware design. We can claim that a lot of the approaches found in the literature suffer from a lack of interdisciplinary interaction among researchers of both evolutionary computation and hardware design fields. In addition, we have also detected that some multi‐objective problems do not use the appropriate algorithms. Copyright © 2012 John Wiley & Sons, Ltd.